(untitled) (American Journal of Islam and Society, 2023)
Over fifty years into global environmental negotiations since the first UN Conference in 1972 on the Human Environment in Stockholm, to the Climate Change Conference COP27 in Sharm El Sheikh in 2022, the major environmental concerns of our time are no closer to being resolved. Negotiations continued to fall by the wayside. Given the commitment to economic development and sovereignty of the nation states, the deadlocks are understandable. Against this background, this article proposes a “Green Caliphate” as a faith-motivated global environmental governance for a network of Sharia-based countries and devout local Muslim communities around the world. The article offers a set of rationales for considering the Green Caliphate in the light of climate emergency from multiple perspectives: social justice, knowledge sharing, and cultural transformation. Drawing on Schumacher’s Small is Beautiful and Ovamir Anjum’s “Who Wants the Caliphate”, this article broaches the concept of a socially and environmentally-responsible caliphate governance which might be in congruent with the Schumacherian pursuit of the “Fourth World” where government and economics are under genuine human control because the size of such units are small, sensible, and human scale, and where the pace of development is in accordance with the religious cosmology of their members to adapt. The Green Caliphate is envisioned on a decolonial horizon of pluriversality towards a multipolar world order. In the cycle of nature there is no such things as victory or defeat; there is only movement. Within that cycle there are neither winners nor losers, there are only stages that must be gone through. Both will pass. One will succeed the other, and the cycle will continue until we liberate ourselves from the flesh and find the Divine Energy. —Paulo Coelho, “Manuscript Found in Accra”